2015
DOI: 10.1152/ajpheart.00635.2014
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and gefitinib-sensitive regulation of cardiac cytokine expression via chronic β-adrenergic receptor stimulation

Abstract: Chronic stimulation of β-adrenergic receptors (βAR) can promote survival signaling via transactivation of epidermal growth factor receptor (EGFR) but ultimately alters cardiac structure and contractility over time, in part via enhanced cytokine signaling. We hypothesized that chronic catecholamine signaling will have a temporal impact on cardiac transcript expression in vivo, in particular cytokines, and that EGFR transactivation plays a role in this process. C57BL/6 mice underwent infusion with vehicle or iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Accumulating evidence suggests that NR4A receptors play essential roles in the development of atherosclerosis, restenosis, and angiogenesis (17,18,33). However, the functional role of the NR4A receptor in cardiomyocyte biology remains largely obscured, although several studies suggest that the NR4A receptors are highly expressed in the heart and that their expression is regulated by several external pathological stimuli, such as oxidative stress, pressure overload, and ␤-AR activation (19,20,34). In the present study, we sought to examine the role of Nur77 in cardiac hypertrophy and found that the expression of Nur77 is substantially increased in response to a wide range of hypertrophic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that NR4A receptors play essential roles in the development of atherosclerosis, restenosis, and angiogenesis (17,18,33). However, the functional role of the NR4A receptor in cardiomyocyte biology remains largely obscured, although several studies suggest that the NR4A receptors are highly expressed in the heart and that their expression is regulated by several external pathological stimuli, such as oxidative stress, pressure overload, and ␤-AR activation (19,20,34). In the present study, we sought to examine the role of Nur77 in cardiac hypertrophy and found that the expression of Nur77 is substantially increased in response to a wide range of hypertrophic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic mice expressing ␤ 1 AR with a G protein-coupled receptor kinase mutation fail to induce EGFR transactivation and develop left ventricular dilation and cardiac dysfunction when treated with isoproterenol. Similarly, mice cotreated with isoproterenol and erlotinib experience increased myocardial apoptosis, left ventricular dilation, and decreases in cardiac function; gefitinib, another EGFR TKI, prevents cardiac hypertrophy as a result of isoproterenol treatment but stimulates cardiac fibrosis when used alone (193) (FIGURE 7). …”
Section: Role Of Egfr In the Heartmentioning
confidence: 99%
“…Furthermore, mice co-treated with isoproterenol and erlotinib show marked reduction in fractional shortening, increased left ventricular diastolic dimension, and an increase in myocardial apoptosis (92). In contrast, gefitinib blocks cardiac hypertrophy induced by isoproterenol in these mice, but also induces cardiac fibrosis when treated alone (109). …”
Section: Heartmentioning
confidence: 99%